Importance of pharmacokinetic studies in the management of acquired factor X deficiency. (18th May 2015) - Lim, Ming Y.; McCarthy, Timothy; Chen, Sheh‐Li; Rollins‐Raval, Marian A.; Ma, Alice D.
Abstract: Up to 14% of individuals with systemic AL amyloidosis develop acquired factor X deficiency, which occurs due to adsorption of factor X onto amyloid fibrils. Although baseline factor X levels are not predictive of bleeding risk in these patients, serious hemorrhagic complications can occur, particularly during invasive procedures. Optimal management strategies to attenuate bleeding risk in these patients are unknown. We describe our experience in the management of acquired factor X deficiency, secondary to systemic AL amyloidosis, in a case series of three patients who received prothrombin complex concentrates (PCCs) for treatment and prevention of bleeding events. We performed a retrospective review extracting information on baseline demographics, laboratory data, pharmacokinetic (PK) studies, and clinically documented bleeding events. Our case series demonstrates that individuals with acquired factor X deficiency secondary to amyloidosis have variable laboratory and clinical responses to PCCs. This is likely due to distinct amyloid loads and fibril sequences, leading to different binding avidities for factor X. Our data emphasize the importance of performing PK testing prior to any invasive procedures to determine the dose and frequency interval to achieve adequate factor X levels for hemostasis, given the variable response between individuals.